2018
DOI: 10.1158/1940-6207.capr-17-0267
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-GMP–Elevating Agents Suppress Polyposis in ApcMin Mice by Targeting the Preneoplastic Epithelium

Abstract: The cGMP signaling axis has been implicated in the suppression of intestinal cancers, but the inhibitory mechanism and the extent to which this pathway can be targeted remains poorly understood. This study has tested the effect of cGMP-elevating agents on tumorigenesis in the mouse model of intestinal cancer. Treatment of mice with the receptor guanylyl-cyclase C (GCC) agonist linaclotide, or the phosphodiesterase-5 (PDE5) inhibitor sildenafil, significantly reduced the number of polyps per mouse (67% and 50%,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
5
29
0
Order By: Relevance
“…18,19,34 Conversely, luminal replacement of GUCY2C agonists reduces the number and size of tumors driven by Apc mutations in mice. 26,32,33,35 These observations support the hypothesis that guanylin loss and silencing of the GUCY2C axis is one molecular mechanism contributing to the progression of tumorigenesis initiated by mutant APC-β-catenin-TCF signaling.…”
Section: Apc-β-catenin-tcf Signaling Regulates Guanylin Nuclear Transsupporting
confidence: 61%
“…18,19,34 Conversely, luminal replacement of GUCY2C agonists reduces the number and size of tumors driven by Apc mutations in mice. 26,32,33,35 These observations support the hypothesis that guanylin loss and silencing of the GUCY2C axis is one molecular mechanism contributing to the progression of tumorigenesis initiated by mutant APC-β-catenin-TCF signaling.…”
Section: Apc-β-catenin-tcf Signaling Regulates Guanylin Nuclear Transsupporting
confidence: 61%
“… 47 , 51 While the underlying mechanism is poorly understood, preclinical evidence suggests that secreted epithelial cGMP has a dampening effect on neural afferents in the lamina propria. 52 54 Increasing cGMP in the intestinal epithelium has also been shown by extensive preclinical studies to suppress intestinal carcinogenesis 55 58 and promote barrier function in the colon. 59 61 These intriguing findings underscore the clinical potential of GC-C agonists for treating post-infectious IBS, ulcerative colitis, and for chemoprevention of colorectal cancer.…”
Section: Discussionmentioning
confidence: 97%
“…8,9 Indeed, trial data found that proton pump inhibitor use in this patient population decreased the risk of gastrointestinal events without a detectable increase in cardiovascular risk; thus, avoidance of proton pump inhibitors in this setting was actually associated with overall clinical harm. Residual confounding likely plays some role in these disparate results and, [10][11][12] unfortunately, "positive" findings from small, early studies are also often more memorable (and more often repeated) than later "negative" findings from larger, more definitive evaluations. 10…”
Section: Conflicts Of Interestmentioning
confidence: 99%